IMC antecedents and the consequences of planned brand identity in higher education. (10th April 2017) - Foroudi, Pantea; Dinnie, Keith; Kitchen, Philip J.; Melewar, T. C.; Foroudi, Mohammad M.
Abstract : Purpose: This study aims to identify integrated marketing communication (IMC) antecedents and the consequences of planned brand identity in the context of higher education, and empirically test a number of hypotheses related to the constructs of these antecedents and consequences. Design/methodology/approach: A model of the IMC antecedents and consequences of planned brand identity was tested in a survey conducted among stakeholders in two London-based universities. Structural equation modelling (SEM) was applied to gain insight into the various influences and relationships. Findings: The study identifies and confirms key constructs in planned brand identity. IMC antecedents of planned brand identity, such as brand elements, service attributes, public relations and place/country of origin, were found to positively influence the planned brand identity consequences of awareness, image and reputation. However, websites, social media, advertising and direct marketing were not found to have significant influence. Research limitations/implications: The focus on two UK universities limits the generalisability of the findings. Future research should be conducted in other country settings to test the relationships identified in the present study. Also, future research may build on the study's findings by investigating the attitudinal and behavioural consequences of brand identification in the higher education context. Practical implications: Professionals responsible for universities' promotional and branding activities need to evaluate the relative contributions of the IMC antecedents of planned brand identity. Brand elements such as design, colour and name, for example, should be reviewed to determine whether modifications are required in different international markets. The increasing prevalence of social media, one of the key antecedents of brand awareness, offers opportunities for universities to engage in brand co-creation by interacting with past, present and future students on relevant digital platforms. Finally, the place/country-of-origin cue is of particular relevance to institutions of higher education given the increasing numbers of students at both undergraduate and postgraduate levels who are choosing to study abroad (Melewar and Akel, 2005). The attraction of the UK as a country to study in, or the appeal of individual cities such as London, should be fully integrated into universities' IMC strategies. Originality/value: The study makes two main contributions. First is the theoretical contribution by identifying the core IMC antecedents and consequences of planned brand identity for universities and from this extrapolate key directions for future research. Second it is indicated that a number of managerial implications are designed to assist in the formulation of improved professional practice.